Reduced CSF p-Tau(181) to Tau ratio is a biomarker for FTLD-TDP - Hu, William T. (Lippincott Williams & Wilkins, 2013)
OBJECTIVES: To validate the ability of candidate CSF biomarkers to distinguish between the 2 main forms of frontotemporal lobar degeneration (FTLD), FTLD with TAR DNA-binding protein 43 (TDP-43) inclusions (FTLD-TDP) and FTLD with Tau inclusions (FTLD-Tau). METHODS: Antemortem CSF samples were collected from 30 patients with FTLD in a single-center validation cohort, and CSF levels of 5 putative FTLD-TDP biomarkers as well as levels of total Tau (t-Tau) and Tau phosphorylated at threonine 181 (p-Tau(181)) were measured using independent assays. Biomarkers most associated with FTLD-TDP were then tested in a separate 2-center validation cohort composed of subjects with FTLD-TDP, FTLD-Tau, Alzheimer disease (AD), and cognitively normal subjects. The sensitivity and specificity of FTLD-TDP biomarkers were determined. RESULTS: In the first validation cohort, FTLD-TDP cases had decreased levels of p-Tau(181) and interleukin-23, and increased Fas. Reduced ratio of p-Tau(181) to t-Tau (p/t-Tau) was the strongest predictor of FTLD-TDP pathology. Analysis in the second validation cohort showed CSF p/t-Tau ratio <0.37 to distinguish FTLD-TDP from FTLD-Tau, AD, and healthy seniors with 82% sensitivity and 82% specificity. CONCLUSION: A reduced CSF p/t-Tau ratio represents a reproducible, validated biomarker for FTLD-TDP with performance approaching well-established CSF AD biomarkers. Introducing this biomarker into research and the clinical arena can significantly increase the power of clinical trials targeting abnormal accumulations of TDP-43 or Tau, and select the appropriate patients for target-specific therapies. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that the CSF p/t-Tau ratio distinguishes FTLD-TDP from FTLD-Tau.